Evaluating the Implementation and Impact of Policy, Practice, and Environmental Changes to Prevent Childhood Obesity in 49 Diverse Communities. (May 2015) - Brennan, Laura K.; Kemner, Allison L.; Donaldson, Kate; Brownson, Ross C.
Abstract : Background: The purpose of this article is to assess and understand the intervention reach, dose, and impact of policy, practice, and environmental changes implemented by the 49 Healthy Kids, Healthy Communities (HKHC) community partnerships across the United States and in Puerto Rico. These partnerships planned and implemented healthy eating and active living policy, system, and environmental interventions to support healthier communities for children and families, with special emphasis on reaching children at highest risk for obesity. Methods: Using a mixed-methods, participatory evaluation design, investigators analyzed multiple qualitative and quantitative data sources collected during the HKHC initiative from 2009 to 2014. Evaluators used an inductive approach to develop indicators to assess intervention reach, dose, and impact for 6 cross-site strategies, including corner stores, farmers' markets, child care nutrition standards, child care physical activity standards, active transportation, and parks and play spaces. Results: Across HKHC community partnerships, 4261 policy, practice, or environmental changes occurred in 1536 intervention settings. Several trends emerged from the data related to how different levels of intervention (ie, community-level, setting-level, and within-setting), the size and access to intervention settings, the stage of implementation, and the sociodemographic composition of the intervention settings play important roles in the way policy, practice, and environmental changes "count" toward intervention reach, dose, and impact. Conclusions: This exploratory analysis provided a method and typology for increasing understanding in the field related to the reach, dose, and impact of policy, practice, and environmental changes promoting healthy eating and active living in order to reduce childhood overweight and obesity. Abstract : Supplemental Digital Content is Available in the Text.This article describes an exploratory analysis of indicators from the evaluation data sources to assess intervention reach, dose, and impact for 6 healthy eating and active living strategies reflecting a range of policy, practice, and environmental changes occurring in the 49 HKHC communities.